Follistatin treatment modifies DNA methylation of the CDX2 gene in bovine preimplantation embryos - Ashry, Mohamed (Mol Reprod Dev, 2020)
CDX2 plays a crucial role in the formation and maintenance of the trophectoderm epithelium in preimplantation embryos. Follistatin supplementation during the first 72 hr of in vitro culture triggers a significant increase in blastocyst rates, CDX2 expression, and trophectoderm cell numbers. However, the underlying epigenetic mechanisms by which follistatin upregulates CDX2 expression are not known. Here, we investigated whether stimulatory effects of follistatin are linked to alterations in DNA methylation within key regulatory regions of the CDX2 gene. In vitro-fertilized (IVF) zygotes were cultured with or without 10ng/ml of recombinant human follistatin for 72 hr, then cultured without follistatin until Day 7. The bisulfite-sequencing analysis revealed differential methylation (DM) at specific CpG sites within the CDX2 promoter and intron 1 following follistatin treatment. These DM CpG sites include five hypomethylated sites at positions −1384, −1283, −297, −163, and −23, and four hypermethylated sites at positions −1501, −250, −243, and +20 in the promoter region. There were five hypomethylated sites at positions +3060, +3105, +3219, +3270, and +3545 in intron 1. Analysis of transcription factor binding sites using MatInspector combined with a literature search revealed a potential association between differentially methylated CpG sites and putative binding sites for key transcription factors involved in regulating CDX2 expression. The hypomethylated sites are putative binding sites for FXR, STAF, OCT1, KLF, AP2 family, and P53 protein, whereas the hypermethylated sites are putative binding sites for NRSF. Collectively, our results suggest that follistatin may increase CDX2 expression in early bovine embryos, at least in part, by modulating DNA methylation at key regulatory regions.